PROSPEK PENGEMBANGAN INDUSTRI PENGASAPAN IKAN SALAI DI DESA PENYASAWAN KECAMATAN KAMPAR - Azri, Rivaldi; Kornita, Sri Endang; Pailis, Eka Armas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted in Kampar Village Penyasawan Village discussing about Prospect of Smoking Salted Fish Industry Development in Kampar Subdistrict Village. The purpose of this study is to determine whether the salting industry is feasible to be developed.Data analysis method used in this research is Net Present Value analysis, Benefit Cost Ratio, Internal Rate of Return and Payback Period. Methods of data collection is done by collecting secondary data data that can be from relevant agencies and with interviews and questionnaires.The results of this study show: 1) from the aspect of industry finances worthy of development seen from the value of NPV is Rp. 325,761,387 which is greater than zero, Benefit Cost Ratio 1.04 which means greater than 1, Internal Rate of Return 26.42% The figure is greater than the interest rate used is 12% and Payback Period obtained 1 year result 2 2) from the aspect of the market has entered the market in and outside Riau Province, 4) from the technical aspects, choosing the location close to the source of raw materials, 5) from the management aspect has been done, 6) from environmental aspects, not polluting the air, 7) From the economic and social aspects of reducing unemploymentKeywords : development prospects